2018
DOI: 10.1080/00207284.2018.1442225
|View full text |Cite
|
Sign up to set email alerts
|

Group Psychotherapy in Specialty Clinics for Substance Use Disorder Treatment: The Challenge of Ethnoracially Diverse Clients

Abstract: Minimal research has explored how clinicians address race and ethnicity considerations in the context of group psychotherapy within substance use disorder (SUD) specialty treatment settings. This article is an exploratory qualitative study in an effort to narrow this gap, using data from semi-structured interviews with 13 group clinicians at three outpatient SUD specialty clinics in the United States. Results are drawn from the portion of coded material pertaining to ethnoracial considerations. A predominant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This research demonstrated an enhancement in the QoL in the social and environmental dimensions, with one of the programs being group and family therapy. The results of this study align with previous research that has highlighted the therapeutic benefits of group therapy, including the fostering of social support, reduction of stigma and isolation, improvement of interpersonal and communication skills, and practice of recovery-focused coping techniques with group members (Wendt & Gone, 2013). Similarly, family or couples counseling can address concerns and improve communication within the family unit, and can also assist in identifying and addressing psychological and behavioral issues that may hinder recovery from substance abuse (Daley, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…This research demonstrated an enhancement in the QoL in the social and environmental dimensions, with one of the programs being group and family therapy. The results of this study align with previous research that has highlighted the therapeutic benefits of group therapy, including the fostering of social support, reduction of stigma and isolation, improvement of interpersonal and communication skills, and practice of recovery-focused coping techniques with group members (Wendt & Gone, 2013). Similarly, family or couples counseling can address concerns and improve communication within the family unit, and can also assist in identifying and addressing psychological and behavioral issues that may hinder recovery from substance abuse (Daley, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Fourth, the use of such an approach requires empathy and sensitivity, particularly when dealing with patients with high levels of distress or facing severe adversity (Langeland and Vinje, 2017), as otherwise exhortations to accept suffering or adapt to it may be misunderstood or rejected (Kizilhan and Wenzel, 2020;Wong, 2020). Fifth, the broad principles outlined in this article need to be adapted to the social, cultural and economic realities of specific situations, to ensure their acceptance by individuals and communities (Wendt and Gone, 2018;Furlong and Finnie, 2020).…”
Section: Existential Positive Psychology (Pp20)mentioning
confidence: 99%
“…A separate study found that organizations that adopted culturally competent practices had reduced wait times for and longer retention of Black and Hispanic clients (31). Unfortunately, prior studies suggest culturally competent practices may be uncommon in SUD facilities (31,33,34). For example, only 18% of SUD treatment facilities in a recent national study reported providing LGBT-speci c programming (35).…”
Section: Discussionmentioning
confidence: 99%